Leadership Role In Implementation Of Lean Manajemen In Hospital - Gita Maera Nurjanah; Qurrotul Aini (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Hospitals in Indonesia are facing the era of JKN (National Health Insurance) with a focus on cost efficiency and service quality, where the implementation of Lean management has been proven to successfully increase patient satisfaction, reduce waiting time, and decrease medical errors. This study aims to synthesize the research findings on the role of leadership in the success of Lean management in hospitals during the period of 2018-2023. The research design used in this article is scoping review. The selection method in this review is guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol. Article search was performed through international journal databases including Google Scholar, PubMed, Sciencedirect, and Emerald published between 2018-2022. The result shows a total of 176 articles were obtained from four databases, namely Google Scholar, PubMed, Sciencedirect, and Emerald. Selection was performed, and 20 articles were considered eligible and included in the systematic review. Leadership, including lean leadership and management, plays a crucial role in the success of Lean management implementation in hospitals, with transformational leadership style recognized as the most effective, but it requires long-term commitment and faces challenges of resistance to change and lengthy implementation time. Keywords: Hospital, Implementation, Leadership, Lean Management, Meta-Analysis.